Identifying priority conservation landscapes and actions for the Critically Endangered Javan leopard in Indonesia: Conserving the last large carnivore in Java Island. - Hariyo Tabah Wibisono; Hariyawan Agung Wahyudi; Erwin Wilianto; Irene Margareth Romaria Pinondang; Mahendra Primajati; Darmawan Liswanto; Matthew Linkie (PLoS ONE)
With the extirpation of tigers from the Indonesian island of Java in the 1980s, the endemic and Critically Endangered Javan leopard is the island's last remaining large carnivore. Yet despite this, it has received little conservation attention and its population status and distribution remains poorly known. Using Maxent modeling, we predicted the locations of suitable leopard landscapes throughout the island of Java based on 228 verified Javan leopard samples and as a function of seven environmental variables. The identified landscapes covered over 1 million hectares, representing less than 9% of the island. Direct evidence of Javan leopard was confirmed from 22 of the 29 identified landscapes and included all national parks, which our analysis revealed as the single most important land type. Our study also emphasized the importance of maintaining connectivity between protected areas and human-modified landscapes because adjacent production forests and secondary forests were found to provide vital extensions for several Javan leopard subpopulations. Our predictive map greatly improves those previously produced by the Government of Indonesia's Javan Leopard Action Plan and the IUCN global leopard distribution assessment. It shares only a 32% overlap with the IUCN range predictions, adds six new priority landscapes, all with confirmed presence of Javan leopard, and reveals an island-wide leopard population that occurs in several highly fragmented landscapes, which are far more isolated than previously thought. Our study provides reliable information on where conservation efforts must be prioritized both inside and outside of the protected area network to safeguard Java's last remaining large carnivore.